گوتاری سیاسی لە ڕۆمانی (دەریاس و لاشەکان)ی بەختیار عەلی‌دا - حسین, هیوا کەریم (Sulaimani Journal for Humanities, 2021)
The Discussion is a philosophical genre, after the postmodernist analysist movement has founded, this genre is developed as a part of humanism studies, especially after the publishing of about conversations by the famous French philosopher, Michel Foucault but still it does not mean he is the founding father of this genre! Historically speaking it has a great track record. Our study is on “Political Discussion in Daryas and its Bodies Novel by Bekhtiar Ali” It is only a step to show one of discussion/conversation genre which is Political Discussion/ or conversation. Our Aim is designated by the Kurdish political society and perspectives in order to catch this genre as a study we had to consider this forced view in the analyzed novel. Our study is titled in two parts; first is the Introductory of Political Conversation and Literature theoretically. This part is subtitled also in two; one is about a trial to analyze the terms in political discussions and the historical routes of the genre. The second is only a work comparison of the genre in both politics and literature. The second title; it’s more practical part of the study that shows political perspectives inside the Daryas and the Bodies novel. In this titled practical study, we included more than several subtitled slices, including Home, Revolution and the holiness of the Kurdish Leaders in Kurdish Society, we provided all needed samples for each subs. At the end the results are displayed in numeral bullets with the listed sources.